Nutritional Literacy for Individual Oral Health Among Village Health Volunteers in Public Health Region 1 of Thailand - Chollada Sorasak; Worayuth Nak‐Ai; Choosak Yuennan; Mansuang Wongsapai (Health Care Science)
ABSTRACT Background Oral health issues persistently affect the overall health and well‐being of rural populations. Village health volunteers (VHVs) play a crucial role in advancing oral health literacy in their community. This study aimed to examine the factors related to nutritional literacy for oral health among VHVs. Methods This was a mixed‐methods study employing an explanatory sequential design. The quantitative data were gathered through questionnaires distributed to a cohort of 10,514 VHVs registered in Health Region 1. A stratified random sampling technique was used to ensure adequate representation of various subgroups within the VHV population, considering factors such as age, education level, and geographical distribution across the region. This approach allowed for a more representative sample that accurately reflects the diversity of the VHV population. Qualitative data were obtained through semi‐structured interviews with a purposive sampling of 20 participants based on specific criteria. Quantitative data were analyzed using descriptive statistics and biserial correlation techniques, while qualitative data were analyzed using content analysis. Results The study found that the sample group possessed a moderate level of knowledge of health literacy principles and nutrition for oral health. However, their self‐assessed skills in nutritional literacy for oral health were rated as high. A statistically significant negative correlation was found between knowledge of nutrition for oral health and skills in nutritional literacy for oral health. VHVs equated health literacy with knowledge because their public health training had focused more on imparting knowledge rather than developing skills based on health literacy principles. Conclusion There is a need to emphasize skill‐based health literacy training and to use effective skill development techniques that are tailored to the specific roles and responsibilities of health volunteers. It is also recommended to continuously monitor and evaluate the outcomes of these efforts.